2005
DOI: 10.1016/j.jcrs.2004.05.050
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of apparent ectasia of the posterior surface of the cornea after keratorefractive surgery

Abstract: The results correspond to the amount of ectasia in previous reports. This artifact may explain the apparent ectasia detected by Orbscan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 11 publications
1
30
0
1
Order By: Relevance
“…To date, studies of posterior changes in eyes with keratoconus were performed using scanning-slit technology, which has been shown to be inaccurate for some posterior corneal measurements in eyes that have had laser in situ keratomileusis (LASIK). [12][13][14][15][16] A fairly recent advance in corneal topography was the introduction of Scheimpflug photography for corneal topographic characterization; this technique allows the study of both the anterior and posterior corneal surfaces 17 and provides more repeatable and reproducible anterior and posterior measurements of corneal power than scanning-slit technology. Kawamorita et al 18 reported 0.19 of agreement for withinrater consecutive measurements of posterior corneal power measurements of diopter (D) with a Scheimpflug-based system and 0.96 D with a scanning-slit system and for between-rater measurements, of 0.56 D and 1.58 D, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…To date, studies of posterior changes in eyes with keratoconus were performed using scanning-slit technology, which has been shown to be inaccurate for some posterior corneal measurements in eyes that have had laser in situ keratomileusis (LASIK). [12][13][14][15][16] A fairly recent advance in corneal topography was the introduction of Scheimpflug photography for corneal topographic characterization; this technique allows the study of both the anterior and posterior corneal surfaces 17 and provides more repeatable and reproducible anterior and posterior measurements of corneal power than scanning-slit technology. Kawamorita et al 18 reported 0.19 of agreement for withinrater consecutive measurements of posterior corneal power measurements of diopter (D) with a Scheimpflug-based system and 0.96 D with a scanning-slit system and for between-rater measurements, of 0.56 D and 1.58 D, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…They show that Orbscan II yields larger posterior corneal elevation values after surgery than Pentacam. Nawa et al 31 report that the apparent ectasia detected by Orbscan may be an artifact. Our results regarding the superior accuracy of Pentacam in the measurement of postoperative pachymetry may indicate that Pentacam is also superior in the analysis of the postoperative posterior corneal surface.…”
Section: Discussionmentioning
confidence: 99%
“…However, the Orbscan's limitations and possible sources of error have been discussed in several studies 1,4,9,10,13,15,19,20 and some authors reason that keratectasia detected by this device is an artifact. As most studies of posterior corneal surface changes after refractive surgery are based on Orbscan examinations, the prevalence and extent of posterior corneal changes after refractive surgical procedures may be overrated.…”
Section: Dpentacammentioning
confidence: 99%